Addressing Criticisms of Large-Scale Marine Protected Areas. (5th April 2018) - O'Leary, Bethan C; Ban, Natalie C; Fernandez, Miriam; Friedlander, Alan M; García-Borboroglu, Pablo; Golbuu, Yimnang; Guidetti, Paolo; Harris, Jean M; Hawkins, Julie P; Langlois, Tim; McCauley, Douglas J; Pikitch, Ellen K; et al.
Abstract: Designated large-scale marine protected areas (LSMPAs, 100, 000 or more square kilometers) constitute over two-thirds of the approximately 6.6% of the ocean and approximately 14.5% of the exclusive economic zones within marine protected areas. Although LSMPAs have received support among scientists and conservation bodies for wilderness protection, regional ecological connectivity, and improving resilience to climate change, there are also concerns. We identified 10 common criticisms of LSMPAs along three themes: (1) placement, governance, and management; (2) political expediency; and (3) social–ecological value and cost. Through critical evaluation of scientific evidence, we discuss the value, achievements, challenges, and potential of LSMPAs in these arenas. We conclude that although some criticisms are valid and need addressing, none pertain exclusively to LSMPAs, and many involve challenges ubiquitous in management. We argue that LSMPAs are an important component of a diversified management portfolio that tempers potential losses, hedges against uncertainty, and enhances the probability of achieving sustainably managed oceans.